PERANCANGAN E-MARKETPLACE DI DINAS KELAUTAN DAN PERIKANAN KABUPATEN TAPUNULI TENGAH - Situmeang, Risky Akbar; Raissa Amanda Putri; Fathiyah Hasyifah Sibarani (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
This study aims to design, create, and assess an electronic market at the Marine and Fisheries Agency of Central Tapanuli Regency as a means to improve the economy of coastal towns. The main objective is to increase market access, product value, and income of coastal communities in the marine and fisheries sector. This R&D system development process uses the Waterfall approach, with the System Usability Scale (SUS) method used to assess user satisfaction. The system was developed using the Laravel framework, CSS, Figma, and MySQL. Suggestions for the long-term development of this e-marketplace include collaboration, local adaptation, and user education. Keywords: E-marketplace, Coastal economy, System Usability Scale (SUS).